The Community Empowerment through Plastic Waste Recycling (Case Study at PKBM Tenggang Raso) Padang City - Rahmadani, Anjeli; Irmawita, Irmawita (Universitas Negeri Padang, 2023)
ABSTRACTThis research is motivated by the existence of plastic waste recycling activities in the community. The aim is to improve community skills so that they can increase knowledge, increase family income and prosper the community in the Pegambiran Ampalu Nan XX sub-district. The purpose of this study is to describe the recycling of plastic waste in terms of its process, form and utilization This research is a research using a qualitative approach, the research method is a case study. The source of the data in this study were the learning residents at the Tenggang Raso PKBM who were the research subjects and the chairmen of this waste recycling activity as research informants. Data collection techniques used in this study are observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and drawing conclusions. Data validity technique is by using source triangulation. The results of the research show that (1) the activity process starts from planning, implementation, mentoring and evaluation, (2) the form of activity is in the form of knowledge, independence and cooperation.